National inception workshop: Agricultural transformation and market integration in the ASEAN region: Responding to food security and inclusiveness concerns: Lao PDR - Southeast Asian Regional Center for Graduate Study and Research in Agriculture (Southeast Asian Regional Center for Graduate Study and Research in Agriculture, 2017)
The International Food Policy Research Institute (IFPRI), the Southeast Asian Regional Center for Graduate Study and Research in Agriculture (SEARCA) and the Department of Agriculture (DOA) organized the National Inception Workshop of the project Agricultural Transformation and Market Integration in the ASEAN Region: Responding to Food Security and Inclusiveness Concerns on 22-23 June 2017. More than 40 experts from international organizations, government agencies, academic institutions, civil society and private sector from Lao PDR, the Philippines, India and the United States of America took part in the discourse on global, regional and national perspectives on agricultural transformation and market integration in the ASEAN region vis-à-vis the Lao PDR economy. The Lao PDR National Inception Workshop had the following objectives: (1) to gain good understanding of the structural transformation and market integration and their implications for agricultural growth and food security in Lao PDR, the position/role of small farmers in ATMI, and the various initiatives to address food security and inclusiveness concerns in Lao PDR; (2) to consult various stakeholders – AMS, civil society organizations (CSOs)/farmers’ organizations (FOs), the private sector, and research institutions on the implementation of the research project on ATMI; (3) to identify priority promising commodities for regional and global value chains; and (4) to develop Country Action Plan towards the achievement of the project’s target outcomes which are enhanced capacity of AMS to identify and design national strategies, policies, programs and national agri-food value chain investment initiatives that benefit small-scale rural producers (SSRPs).